Prevalence of SARS-CoV-2 reinfection-related underlying diseases among permanent residents, 2023: a cross-sectional survey in Henan province - Yafei LI; Yingying WANG; Lin ZHU; Haifeng WANG; Ying YE; Xueyong HUANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo examine the prevalence of underlying diseases potentially associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reinfection among residents in Henan province for developing targeted strategies on the containment of coronavirus disease 2019 (COVID-19) epidemic. MethodsWe carried out a face-to-face survey during March 2023 among 5 200 permanent residents (elder than one year) recruited with multistage random cluster sampling in 10 counties/districts across Henan province. The prevalence of eight uderlying diseases (hypertension, diabetes mellitus, heart disease, cerebral apoplexy, allergic asthma, chronic obstructive pulmonary disease [COPD], neoplasm, and chronic kidney disease [CKD]) potentially associated with SARS-CoV-2 reinfection among the participants were analyzed based on the information collected using a questionnaire having been used by Chinese Center for Disease Control and Prevention. ResultsAmong the 5188 participants with valid responses, 1 253 (24.2%) reported suffering from one or more of the eight underlying diseases and the number (proportion) of the participants suffering from one of the eight diseases were 883 (17.0%) for hypertension, 302 (5.8%) for diabetes mellitus, 254 (4.9%) for cardiac disease, 106 (2.0%) for stroke, 20 (0.4%) for allergic asthma, 17 (0.3%) for COPD, 17 (0.3%) for neoplasm, and 12 (0.2%) for CKD, respectively. There were 283 (5.5%) of the participants reported suffering from two or more of the eight underlying diseases; of the participants having comorbidities, 82.7%, 15.5%, and 1.8% suffered from 2, 3, and 4 of the eight underlying diseases, with the top four multimorbidity patterns of diabetes plus hypertension (reported by 95 [33.6%] of the participants), hypertension plus heart disease (83, 29.3%), hypertension plus stroke (28, 9.9%), and diabetes mellitus plus hypertension and heart disease (24, 8.5%). ConclusionThe prevalence of underlying diseases potentially associated with SARS-CoV-2 reinfection was higher and hypertension was a predominant underlying disease among the residents in Henan province. The results suggest that the risk of SARS-CoV-2 reinfection for persons with underlying diseases needs to be assessed.